A STROBE-compliant case–control study: Effects of cumulative doses of topical atropine on intraocular pressure and myopia progression. Issue 48 (25th November 2020) - Yu, Teng-Chieh; Wu, Tzu-En; Wang, Yuan-Shen; Cheng, Shen-Fu; Liou, Shiow-Wen
Abstract : Abstract: Topical atropine has become a mainstream treatment of myopia throughout East and Southeast Asia, but it is uncertain whether long-term topical atropine therapy induces intraocular pressure (IOP) elevation and subsequent development of glaucoma. We then prospectively examined the effects of long-term atropine treatment on IOP. Our case series collected 186 myopic children who were younger than 16 years of age. Complete ocular examination data, IOP and refractive status measurements beginning in 2008 were collected for all participants. Participants were divided into two groups: 121 children who received atropine therapy at various concentrations were classified as the treated group, whereas 65 children who did not receive atropine therapy were classified as the untreated (reference) group. In the treated group, clinicians prescribed different concentrations of atropine eye drops according to their discretion with regard to the severity of myopia on each visit of the patient. We then calculated the cumulative dose of atropine therapy from 2008 to the patients' last follow-up in 2009. Furthermore, the treated group was then further divided into low- and high-refractive-error groups of nearly equal size for further analysis. There were no significant differences for the baseline refractive errors and IOPs between the treated and untreated groups. Both the low- and high-cumulative atropine dosage subgroups showed significantly lower myopic progression than the untreated group, but there was no significant difference between the two subgroups in terms of different cumulative dosages. All groups, including the untreated group, showed an increase of mean IOP at the last follow-up, but both low- and high-cumulative atropine dosage subgroups experienced a smaller increase of IOP. The mean IOP of all atropine-treated groups showed no significant increase in either low- or high-refractive-error eyes. This study revealed that topical atropine eye drops do not induce ocular hypertension and are effective for slowing the progression of myopia. The treatment effects are not correlated with the cumulative atropine dosages.